Systematic Literature Review – Determinants of Corporate Financial Distress Prediction - Primawan, Ardy (UNIB Press, 2023)
The purpose of this study is to conduct a systematic literature review of the determinants of corporate financial distress prediction, based on scientific papers in related fields, which have been published. This paper tries to provide a thorough review of scientific papers on the topic of predicting the company's financial difficulties, researching, and showing the relationship among authors of different scientific papers and also showing the main determinants used and researched by the authors of these scientific papers in the last 10 years.Systematic literature review (SLR) is carried out using Garuda (Garba Rujukan Digital) as database to obtain scientific papers from a period of 10 years, namely 2012-2022, with the topic of predicting corporate financial distress from listed companies in Indonesia Stock Exchange (IDX). The first finding in this paper is that the prediction of corporate financial distress is a topic that is increasingly attracting the attention of researchers, as evidenced by the increasing number of scientific papers in this topic from year to year. Secondly, that financial ratios are the most influential determinants in the research carried out by authors of scientific papers, in different predictive models they used..